Sepsis from an apheresis platelet contaminated with Acinetobacter calcoaceticus/baumannii complex bacteria and Staphylococcus saprophyticus after pathogen reduction. Issue 9 (1st August 2020) - Fridey, Joy L.; Stramer, Susan L.; Nambiar, Ashok; Moayeri, Morvarid; Bakkour, Sonia; Langelier, Charles; Crawford, Emily; Lu, Thea; Lanteri, Marion C.; Kamm, Jack; Miller, Steve; Wagner, Stephen J.; et al.
Abstract: Background: Strategies to reduce platelet (PLT) bacterial contamination include donor screening, skin disinfection, sample diversion, bacterial culture, pathogen reduction (PR), and day‐of‐transfusion tests. We report bacterial sepsis following a pathogen‐reduced PLT transfusion. Case Report: An adult male with relapsed acute lymphoblastic leukemia was successfully treated for central catheter–associated Staphylococcus aureus bacteremia. A peripherally inserted central catheter (PICC) was placed. Chills, rigors, and flushing developed immediately after PICC‐infused pathogen‐reduced PLTs, progressing to septic shock requiring intensive care management. Methods: PICC and peripheral blood (PB), transfused bag saline flushes (TBFs), environmental samples, and the pathogen‐reduced untransfused co‐component (CC) were cultured. Plasma metagenomic and bacterial isolate whole‐genome sequencing; PLT mitochondrial DNA (mtDNA) testing of untransfused CC and TBF; CC testing for amotosalen (S‐59)/S‐59 photoproducts; isolate PR studies (INTERCEPT); and TBF polymerase chain reaction for recipient Y‐chromosome DNA were performed. Results: PB and PICC cultures grew Acinetobacter calcoaceticus/baumannii complex (ACBC). TBF was gram‐positive; mass spectrometry identified ACBC and Staphylococcus saprophyticus (SS). CC Gram stain and cultures were negative. Environmental cultures, some done after decontamination, were ACBC/SS negative. Posttransfusion patient plasma and TBF ACBC sequences were genetically identical. No Y‐chromosome signal was detected in TBF. S‐59 photoproducts and evidence of mtDNA amplification inhibition were found in the CC. Spiking PR studies showed >5.9‐log inactivation for both isolates. Donor skin cultures for Acinetobacter were negative. Conclusion: CC sterility, PR studies, residual S‐59 photoproducts, and mtDNA amplification inhibition suggest successful PR. Unidentified environmental sources and inherent or acquired bag defects may have contributed to postmanufacturing pathogen‐reduced PLT contamination.